Study of the fungicidal properties of ozone treatment, Ag and Cu nanoparticles and their combined action on the model of sanitary significant mold saprophyte Aspergillus flavus - Taran, G.V.; Kadolin, B.B.; Yaroshenko, M.O.; Stegnii, B.T. (Problems of Atomic Science and Technology, 2023)
A study was conducted to determine the fungicidal activity of a sanitary contaminant of feeds – representatives of the genus Aspergillus Mich. – species of Aspergillus flavus using the ozone treatment method, treatment with the composition of Ag and Cu nanoparticles and the combined effect of these methods. When studying the combined effect of ozone, NPAg and NPCu, it was found that at the concentration ratio of 100:100 μg/cm³, there was a fungicidal effect on museum strains of Aspergillus flavus test cultures, i.e., the combination with ozone enhanced the antifungal properties of nanocomplex. Проведено дослідження з визначення фунгіцидної активності санітарно-значущого контамінанту кормів – представників роду Aspergillus Mich. – вид Aspergillus flavus, озоновим методом обробки розчину, компо зицією наночастинок металів Ag i Cu та сумісною дією цих методів. При дослідженні сумісної дії озону та NPAg і NPCu встановлено, що при концентраційному співвідношенні наночастинок 100:100 мг/см³ має місце фунгіцидна дія щодо музейних штамів тест-культур Aspergillus flavus, тобто комбінація з озоном посилила антимікотичні властивості нанокомплексу.